Highly efficient, free-breathing whole-chest equilibrium phase bT1RESS MR angiography: Initial clinical experience - Robert R. Edelman; Amit Pursnani; Kevin Lee; Hang Chen; Reza Nezafat; Tess Wallace; Nondas Leloudas; Derek Clarke; Ioannis Koktzoglou (Journal of Cardiovascular Magnetic Resonance)
Background: A fundamental limitation of both computed tomography angiography (CTA) and contrast-enhanced MRA (CEMRA) is that angiographic image quality greatly deteriorates when scans are obtained after the first pass, so that the useful post-contrast scan window is limited to a few tens of seconds. To overcome this limitation, we recently described a breath-hold, slab-selective technique called equilibrium phase balanced T1 relaxation-enhanced steady-state (bT1RESS) that permits diagnostic CEMRA to be obtained for tens of minutes after contrast agent infusion. Further improving upon this technique, we implemented a highly efficient free-breathing version for very rapid whole-chest imaging and tested it in a series of patients. Main body: This study was IRB approved. 34 patients with cardiovascular indications were imaged using a standard CMR protocol plus a post-contrast prototype navigator-gated, whole-chest bT1RESS sequence using either 2×2 or 3×2 (slice x phase) generalized autocalibrating partially parallel acquisition (GRAPPA) acceleration. Results: Median scan time for 20 patients using 3×2 acceleration was 1.25 min vs. 2.21 min for 14 patients using 2×2 acceleration. Mean blood pool-to-muscle signal intensity ratio for bT1RESS obtained >20 min post-contrast was 88% of the value for scans obtained <5 min post-contrast. Inline reconstruction time for a complete 128-slice data set was <15 s. Good-to-excellent image quality and visualization of the aorta, pulmonary arteries and veins, coronary origins, coronary sinus, left atrial appendage, atria and ventricles were obtained in all cases with 3×2 acceleration and all but one case with 2×2 acceleration. There was also excellent correlation (0.92/0.93, p<0.001) between left/right end-diastolic ventricular volumes obtained from short axis cine stacks vs. bT1RESS, and good-to-excellent correlation (0.84/0.64), p<0.001) for left/right end-diastolic atrial volumes. Discussion and conclusion: Free-breathing, whole-chest bT1RESS shows promise as a highly efficient and useful method for cardiovascular imaging. Diagnostic quality scans can be acquired regardless of post-contrast scan delay. Given the very short scan and reconstruction times, navigator-gated bT1RESS can be easily incorporated into any CMR protocol to allow volumetric evaluation of the thoracic vasculature and heart. With further development, the technique could also prove useful for rapid 3D functional evaluation of the heart.